An overview of the traditional rice-prawn-fish farming in Kalia of Narail district, Bangladesh - Shams Muhammad Galib; ABM Mohsin; Nipa Chaki; Md. Foyzul Hassan Fahad; Sk. Md. Mohaimenul Haque (Journal of Fisheries, 2013)
This study was conducted in Narail district, Bangladesh between January and June, 2012; with a view to describing the status of rice- prawn-finfish based aquaculture practices. Average area of plots was 0.55±0.44 ha, of which mean ditch area was 4.35±2.02% of total land. All farmers dry their plots and made renovation prior to start of a new growing season followed by liming and fertilization. No standard stocking density was maintained, prawns were stocked at 15895 PL/ha, whereas fin fishes at 1551 seeds/ha. Commercial feed was applied in all the plots. Production of prawn, stocked and non-stocked fin fishes were found 380.34±155.25 kg/ha; 713.65±352.99 kg/ha and 51.73±24.55 kg/ha respectively. Average cost and income for fish culture were 120514.07±36758.35 BDT/ha and 232497.48±76594.80 BDT/ha respectively. Average rice production was 4229.78±856.71 kg/ha. Low growth and high mortality of PL; scarcity, high and uprising price of feeds; and floods were identified as the major problems.